Microwave-assisted heating in a novel thin film-liquid spinning coaxial reactor - Guennadi A. Kouzaev (AIMS Electronics and Electrical Engineering)
This paper introduces a novel rotating reactor designed for microwave-assisted heating and chemical processes. It consists of a sealed coaxial waveguide with a dielectric hollow mixer that rotates along the length of the central conductor. A heating liquid flows in a narrow gap between this rotor and the outer shield of the coaxial waveguide, powered by microwaves. It is hypothesized that the acceleration of the conversation rate of chemical reactions is due to the excitation of micro-vortices for better mixing and the direct application of microwaves to a mix of polar reagents within the narrow gap. This study presents initial experimental results of microwave liquid heating, hydrodynamics, and mechanics in this reactor.